A road to future broadband wireless access MIMO-OFDM-Based air interface. - Hongwei Yang (IEEE Communications magazine)
Orthogonal frequency-division multiplexing is a popular method for high-data-rate wireless transmission. OFDM may be combined with multiple antennas at both the access point and mobile terminal to increase diversity gain and/or enhance system capacity on a time-varying multipath fading channel, resulting in a multiple-input multiple-output OFDM system. In this article we give a brief technical overview of MIMO-OFDM system design. We focus on various research topics for the MIMO-OFDM-based air interface, including spatial channel modeling, MIMO-OFDM transceiver design, MIMO-OFDM channel estimation, space-time techniques for MIMO-OFDM, and error correction code. The corresponding link-level simulation results are encouraging, and show that MIMO-OFDM is a promising road to future broadband wireless access.